2020
DOI: 10.1021/acschemneuro.9b00617
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Optical Isomers of Methcathinone, and Two Achiral Analogs, at Monoamine Transporters and in Intracranial Self-Stimulation Studies in Rats

Abstract: Methcathinone (MCAT; 1), the progenitor of numerous and widely abused “synthetic cathinone” central stimulants, exists as a pair of optical isomers. Although S(−)­MCAT is several-fold more potent than R(+)­MCAT in rodent locomotor stimulation and in stimulus generalization studies in rat drug discrimination assays, the individual optical isomers of MCAT have never been directly compared for their actions at monoamine transporters that seem to underlie their actions and have never been examined for their relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Davies et al [ 70 ] studied the actions of the enantiomers of methcathinone ( 8 ) at monoamine transporters, discovering that they presented similar inhibition potencies at DAT and NET. At SERT, the S -enantiomer displayed a lower potency than at DAT and NET, while the R -enantiomer was practically inactive.…”
Section: Enantioselectivity Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Davies et al [ 70 ] studied the actions of the enantiomers of methcathinone ( 8 ) at monoamine transporters, discovering that they presented similar inhibition potencies at DAT and NET. At SERT, the S -enantiomer displayed a lower potency than at DAT and NET, while the R -enantiomer was practically inactive.…”
Section: Enantioselectivity Studiesmentioning
confidence: 99%
“…At SERT, the S -enantiomer displayed a lower potency than at DAT and NET, while the R -enantiomer was practically inactive. Furthermore, in this study, an ICSS procedure to evaluate abuse-related drug effects in rats showed that the S -enantiomer presented almost twice the potency of the R -enantiomer [ 70 ].…”
Section: Enantioselectivity Studiesmentioning
confidence: 99%
“…α-Amino ketone is a motif frequently found in bioactive molecules and natural products. Also, it serves as a versatile synthetic intermediate for producing amino alcohols and nitrogen-containing heterocycles. Consequently, the development of efficient methods for constructing α-amino ketones holds multiple implications for organic synthesis. Among various synthetic strategies for α-amino ketones, intermolecular C–C bond formation between the nitrogen-containing substrates and oxygen-containing counterparts is of particular value because it allows efficient construction of diverse carbon skeletons using readily available starting materials.…”
mentioning
confidence: 99%